Pendampingan Suami Dengan Tingkat Kecemasan Ibu Saat Menghadapi Proses Persalinan Di BPS Ny. Hj. Amalia Amd.Keb Simogirang Prambon Sidoarjo - Nursaidah; Eka Kusfarini (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
The support or involvement of the husband is very necessary in a mother's psychological development that facing the birth process. The purpose of this study to determine the relationship between husband assistancy with anxiety on the laboring mother. This was a crossectional study. Assisted by husband as an independent variable and anxiety during labor as the dependent variable. The study population of all labor mothers in BPS Hj.Amalia Amd.Keb Simogirang, Prambon, Sidoarjo as many as 30 maternal. Samples were taken by concecutive sampling of 24 respondents. Data were collected with a questionnaire and tested with the chi square test and presented in tabular form. Results showed that 13 respondents who are not accompanied her husband there was 1 respondent (4.1%) who did not experience anxiety, 7 respondents (29.1%) had anxiety and 5 being the respondents (20.8%) experienced severe anxiety. The results of mann-whitney test data showed that Z = 2,531, Z table = 0.0288, ρ = 0,015 dan α = 0,05 so that ρ < α then H0 rejected and H1 accepted means there is a relationship between husband assistance with the level of anxiety when faced the labor. Husband assistance will give a good impact on psychological wives so that they can perform labor well, safely and smoothly.The results could be used as additional information and insight for the community about the delivery process so as to enhance the knowledge held by the public, especially the husband that will have children so as to determine appropriate action in the face of labor later.